A Research Agenda to Better Understand the Human Dimensions of Energy Transitions - Steg, Linda; Perlaviciute, Goda; Sovacool, Benjamin K.; Bonaiuto, Marino; Diekmann, Andreas; Filippini, Massimo; Hindriks, Frank; Bergstad, Cecilia Jacobbson; Matthies, Ellen; Matti, Simon; Mulder, Machiel; Nilsson, Andreas; et al. (Frontiers in Psychology, 2021)
The Social Sciences and Humanities (SSH) have a key role to play in understanding which factors and policies would motivate, encourage and enable different actors to adopt a wide range of sustainable energy behaviours and support the required system changes and policies. The SSH can provide critical insights into how consumers could be empowered to consistently engage in sustainable energy behaviour, support and adopt new technologies, and support policies and changes in energy systems. Furthermore, they can increase our understanding of how organisations such as private and public institutions, and groups and associations of people can play a key role in the sustainable energy transition. We identify key questions to be addressed that have been identified by the Platform for Energy Research in the Socio-economic Nexus (PERSON, see person.eu), including SSH scholars who have been studying energy issues for many years. We identify three main research themes. The first research theme involves understanding which factors encourage different actors to engage in sustainable energy behaviour. The second research theme focuses on understanding which interventions can be effective in encouraging sustainable energy behaviour of different actors, and which factors enhance their effects. The third research theme concerns understanding which factors affect public and policy support for energy policy and changes in energy systems, and how important public concerns can best be addressed as to reduce or prevent resistance.